Synthetic Method for 2′-Amino-LNA Bearing Any of the Four Nucleobases via a Transglycosylation Reaction - Sawamoto, Hiroaki; Arai, Yuuki; Yamakoshi, Shuhei; Obika, Satoshi; Kawanishi, Eiji (Organic letters, 2018)
A transglycosylation reaction of 2′-amino-locked nucleic acid (LNA) from thymine (T) to other nucleobases adenine (A), guanine (G), and 5-methylcytosine (mC) has been developed. This reaction proceeds in high yield and with high β-selectivity. The mild reaction conditions enable the coexistence of acid-labile protecting groups, including a 4,4′-dimethoxytrytyl (DMTr) group. 2′-Amino-LNAs bearing any nucleobase can now be easily synthesized.